2011
DOI: 10.1007/s00726-011-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte glutathione transferase: a potential new biomarker in chronic kidney diseases which correlates with plasma homocysteine

Abstract: The erythrocyte glutathione S-transferase (e-GST) is a member of a superfamily of inducible enzymes involved in cell detoxification that shows an increased expression in chronic kidney disease (CKD) patients. We propose a new automated analysis procedure for e-GST activity that has been validated in 72 CKD patients and 62 maintenance hemodialysis patients (MHD). Regression analysis was carried out to assess association between e-GST activity data, main clinical variables, and plasma homocysteine (Hcy), a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 28 publications
7
50
1
Order By: Relevance
“…Reports about GPX activity in CKD are inconclusive. Some authors described a positive impact of PD, but others did not find differences compared with HD [21,23,24,28,29,30,31,32,33,34]. Our study showed that renal replacement therapy negatively influences GPX activity.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Reports about GPX activity in CKD are inconclusive. Some authors described a positive impact of PD, but others did not find differences compared with HD [21,23,24,28,29,30,31,32,33,34]. Our study showed that renal replacement therapy negatively influences GPX activity.…”
Section: Discussionsupporting
confidence: 50%
“…In our study there were no significant differences between GST activities among the whole examined groups; however, it was above the normal range. Some authors showed a higher activity of GST in HD than in PD patients [33,34,35]. The HD procedure did not influence this enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other GST isoenzymes are not represented or are below the limit of detection. This conclusion represents a clarification of the contradictory evidence reported previously in this context [7], [8], [10], [12]. Even if other GSTs may be present in trace amounts in saliva, GSTP1-1 clearly represents the most abundant isoenzyme.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, a direct interaction has been described between the GSTP1-1 and the TRAF domain of TNF receptor-associated factor 2 [11]. In addition, a particular GST isoenzyme present in the erythrocytes, the GSTP1-1, is overexpressed in case of increased blood toxicity as it occurs in nephropathic patients [12] and in healthy subjects living in polluted areas [13]. Thus, erythrocyte GSTP1-1 is considered a biomarker of blood toxicity.…”
Section: Introductionmentioning
confidence: 99%